Seasonal Variations in Water Quality of Mandore Region, Jodhpur District, India - Bhutra, M.K.; Purohit, Sangita (Asian Journal of Chemistry, 2012)
A physico-chemical study of the ground water of Mandore region of Jodhpur district has been carried out to examine the suitability of water for drinking and irrigation purposes. Fifty-one water samples representing the ground water of the region were collected during pre- monsoon and post-monsoon seasons in the month of June and November 2011 respectively and were analyzed for physico-chemical characters. The results were used for inter elemental correlation analysis which indicates that most of the elements have good correlation. The quality of water that predominated in the study area was assessed based on hydro-chemical facies. Piper-trilinear and Stiff pattern diagrams were used to find out the hydro-chemical type of ground water, which show that most of them are Na-K-Cl type. Besides, geochemical classification the suitability of ground water for irrigation was evaluated based on sodium adsorption ratio, percent sodium (% Na) and residual sodium carbonate values. The results of study provided information needed for ground water quality management in the region.